Design fabrication and testing of a rainfall simulator - Kurien E K (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1993)
Rainfall simulators are considered as effective aids in soil conservation research. Simulators make it possible to produce predetermined storms at any desired time and location. A rainfall simulator suitable for soil erosion studies was designed and fabricated at KCAET Tavanur. The developed simulator was tested for its performance. Erosion studies on laterite soil was conducted using the developed simulator. The rainfall simulator designed and fabricated was of an oscillating, tubing tip type. The crop former unit consisted of 112 numbers of 18 gauge hypodermic needles fitted on a 1.8 cm GI pipe network. The speed of oscillation was 8 oscillations per minute. The drop former unit was supported at a height of 3 cm above ground level. Intensity of rainfall was varied by changing the pressure of water supply to the simulator. The simulator was tested for intensity, droplet size and uniforimity of application of the rainfall produced. The intensity of rainfall was related to the pressure of water supply as 1 = 6.0386 – 31.9152 P + 177.30 P2 The drop size obtained was 2.31 mm for an intensity of 4.77 cm/hr and the corresponding drop sizes for intensities of 5.60, 6.73, 6.99 and 8.80 cm/hr were 2.20, 2.18, 1.05 and 0.80 m respectively. Christiansen’s uniformity coefficients calculated for intensities ranging from 4.77 to 8.80 cm/hr varied from 82 to 88 per cent. Experiments were also conduced to study soil loss and runoff from laterite soil. The soil loss increased with the intensity of rainfall for all the slopes studied. Maximum soil loss of 1464 kg/ha/hr occurred from a slope 20 per cent at a rainfall intensity of 8.80 cm/hr. A general trend of increase in soil loss with slope was observed. At an intensity of 8.80 cm/hr the soil loss from 5 per cent slope was 940.2 kg/ha/hr whereas the soil loss from 20 per cent slope was 1464 kg/ha/hr for the same intensity. At 5.60 cm/hr intensity of rainfall the runoff from a slope of 5 per cent was 325.33 m3 /ha/hr whereas the runoff was 432 m3 /ha/hr at 6.73 cm/hr intensity for the same slope. Empirical equations were developed for estimating soil erosion and runoff for various intensities of rainfall and land slopes. The equations are : 1. E = -982.384 + 2834.63 S + 225.239 1 (R = 0.94) 2. Q = -216.174 + 1104.65 S + 79.375 1 (R = 0.92)